Large-scale WGS of carbapenem-resistant Acinetobacter baumannii isolates reveals patterns of dissemination of ST clades associated with antibiotic resistance. (25th January 2022) - Frenk, Sammy; Temkin, Elizabeth; Lurie-Weinberger, Mor N.; Keren-Paz, Alona; Rov, Reut; Rakovitsky, Nadya; Wullfhart, Liat; Nutman, Amir; Daikos, George L.; Skiada, Anna; Durante-Mangoni, Emanuele; Dishon Benattar, Yael; et al.
Abstract: Objectives: To describe the population genetics and antibiotic resistance gene distribution of carbapenem-resistant Acinetobacter baumannii (CRAB) isolates causing infections in three Mediterranean countries. Methods: Isolates were collected during the 2013–17 AIDA clinical trial in six hospitals in Israel, Greece and Italy. WGS, bioinformatic characterization and antibiotic resistance profiling were performed. Results: In the 247 CRAB isolates characterized in this study, ST distribution varied by country: 29/31 (93.5%) Greek isolates, 34/41 (82.9%) Italian isolates and 70/175 (40.0%) Israeli isolates belonged to ST2. The identified ST2 isolates included eight distinct clades: 2C, 2D and 2H were significantly more common in Italy, while 2F was unique to Greece. The uncommon ST3 was not present among Greek isolates and constituted only 5/41 (12%) Italian isolates. On the other hand, it was much more common among Israeli isolates: 78/175 (44.6%) belonged to ST3. The vast majority of isolates, 240/247 (97.2%), were found to harbour acquired carbapenemases, primarily bla OXA-23. The chromosomal oxaAb ( bla OXA-51 - like ) and ampC genes characteristic of this organism were also ubiquitous. Most (96.4%) ST3 isolates carried a broad-host-range plasmid IncP1α. Conclusions: The geographical differences in CRAB populations support the theory that clonal spread of CRAB leads to endemicity in hospitals and regions. The close association between antibiotic resistance genes and clades, and between plasmids and STs, suggest that de novo creation of MDR A. baumannii is rare. The clustering of antibiotic resistance genes and plasmids that is unique to each clade/ST, and nearly uniform within clades/STs, suggests that horizontal transmission is rare but crucial to the clade's/ST's success.